1999
DOI: 10.1097/00126334-199905010-00002
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Reactivation in Resting Peripheral Blood Mononuclear Cells of Infected Adults Upon in Vitro CD4 Cross-Linking by Ligands of the CDR2-Loop in Extracellular Domain 1

Abstract: HIV-1 infects resting peripheral blood mononuclear cells (PBMCs) but remains inactive state until subsequent cell activation. We have demonstrated that the cross-linking of cell surface CD4 by gp120-anti-gp120 immune complexes or heat-inactivated HIV-1 (iHIV-1) is sufficient to trigger activation signals leading to virus reactivation (9). In this study, we demonstrate that NF-kappaB nuclear translocation and stimulation of virus production by iHIV-1 were strictly linked to the concentrations of viral proteins … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1
1

Year Published

2000
2000
2007
2007

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 55 publications
0
6
1
1
Order By: Relevance
“…In contrast, HIV-uninfected PBMC treated with either iHIV or soluble gp120 failed to express the cell surface activation markers CD25 and CD69 (30), although a small increase in cellular proliferation was observed 48 h post-treatment with iHIV. The discrepancy between our data and those of the previous studies (24,29,30) with regard to the effects of envelope on cellular activation probably reflect differences in the cellular systems analyzed and, perhaps, the form in which envelope protein is presented. In PBMC an indirect effect on T cell activation may occur following the interaction between gp120/160 and other CD4 ϩ cells, such as monocyte/macrophages.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast, HIV-uninfected PBMC treated with either iHIV or soluble gp120 failed to express the cell surface activation markers CD25 and CD69 (30), although a small increase in cellular proliferation was observed 48 h post-treatment with iHIV. The discrepancy between our data and those of the previous studies (24,29,30) with regard to the effects of envelope on cellular activation probably reflect differences in the cellular systems analyzed and, perhaps, the form in which envelope protein is presented. In PBMC an indirect effect on T cell activation may occur following the interaction between gp120/160 and other CD4 ϩ cells, such as monocyte/macrophages.…”
Section: Discussioncontrasting
confidence: 99%
“…The effect of envelope protein (gp120 or gp120-anti-gp120 complexes) or inactivated HIV (iHIV) virions on HIV expression has been previously investigated using unstimulated PBMC isolated from HIV-infected donors (29) or PBMC infected with HIV in vitro (24). In the earlier study the expression of HIV was associated with a transition to the S/G 2 /M stage of the cell cycle and the expression of the cell surface activation marker CD25 (24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies have addressed the role played by NF‐κB transcription factor in the reactivation of HIV from the latent state and in the control of viral persistence. We previously demonstrated that gp120 env ‐dependent activation of NF‐κB has a significant relevance to the physiopathology of HIV infection by reactivating HIV‐1 transcription in PBMCs from symptomatic infected patients [31]. Besides this, the direct interaction of gp120 env with a CXCR4 receptor was also reported by others to stimulate T cell apoptosis in a CD4‐independent fashion [36].…”
Section: Discussionmentioning
confidence: 85%
“…Our previous papers focused on T cell activation triggered by gp120 env binding to the CD4 receptor and demonstrated that CD4 cross‐linking with gp120 env stimulates both AP‐1 and NF‐κB DNA‐binding activity. The consequences of such activation signals on reactivating latent proviruses harbored by primary T cells from HIV‐1 infected T cells have also been described [31].…”
Section: Discussionmentioning
confidence: 99%